Seed morphology of perennial taxa of Euphorbia section Pithyusa (Euphorbiaceae) in Turkey - Genç İlker; Kültür, Şükran (Phytotaxa, 2018)
A comprehensive study based on seed morphology of perennial Euphorbia (Euphorbiaceae) sect. Pithyusa species occurring in Turkey is presented. A total of 14 species were studied. Seed characteristics were examined using scanning electron microscopy (SEM) as well as dissecting light microscopy. Significant features are: seed size, seed shape, shape of caruncle and seed surface ornamentation. Three different seed surface types (smooth, pitted, and wrinkled) were observed. Four main seed shapes (ovoid, oblong, quadrangular, and globose), as well as seven types of seed coat ornamentation (reticulate-areolate, areolate, alveolate, falsifoveate, pusticulate, colliculate and smooth) were found. The number of testa cells per 100 µm2 and also its range, from 8–12 to 57–63, are given.